Evaluation of the Nutritional Quality of Processed Foods in Honduras: Comparison of Three Nutrient Profiles - Hernandez Santana, Adriana; Waleska Bodden Andrade, Sharyl; Rojas Aleman, Dina; Enríquez, Jean Pierre; Di Iorio, Adriana Beatriz (MDPI, 2020)
Obesity is considered a global pandemic. Different countries have worked to implement front-of-package (FOP) labeling systems that define thresholds for critical nutrients (CN) as part of their public health policies. The objective of this study is to identify the proportion of Processed (PF) and Ultra-Processed (UPF) Foods marketed in Honduras, which meet or fall short of the criteria of three Nutrient Profile Models (NPM): PAHO (2016), Chile (2017) and the Central American Technical Regulation Proposal-Nutritional Warning Front Labeling (CATRP-NWFL 2017). This study is descriptive; 1009 products from 206 brands were collected nationwide. Descriptive statistics were performed. The mean CN compliance with the three models was 49.3% for sodium, 30.6% for sugars, 63.1% and 96% for saturated and trans fats. The PAHO and Chilean (NPM) similarly concentrated on the lower compliance with the established criteria, unlike the CATRP, which has less stringent criteria. This is the first assessment of CN content in PF and UPF in Honduras under three different NPMs. We highlight the importance of defining or adopting criteria for the implementation of NWFL as information for the consumer and thereby contribute to reducing the risks of obesity and related disease